2015
DOI: 10.1021/acs.jpcb.5b03810
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Potential Binding Sites of 3,5,4′-Trihydroxystilbene (Resveratrol) and trans-3,3′,5,5′-Tetrahydroxy-4′-methoxystilbene (THMS) to the GAPDH Molecule Using a Computational Ligand-Docking Method: Structural and Functional Changes in GAPDH Induced by the Examined Polyphenols

Abstract: The presented study analyzed potential binding sites of 3,5,4'-trihydroxystilbene (resveratrol, RSV) and its derivative, trans-3,3',5,5'-tetrahydroxy-4'-methoxystilbene (THMS) to glyceraldehyde 3-phosphate dehydrogenase (GAPDH). The effects of stilbene analogs on the structure of GAPDH were determined by fluorescence spectroscopy and ζ potential measurements. To what extent the studied compounds affect the activity of the enzyme was also assessed. A computational ligand-docking study showed that there are 11 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Reduction of potential amounted from -5.1 ± 0.6 mV in the absence of the ligand to -11.2 ± 0.7 mV in its presence. Previous studies indicated slightly smaller changes of charge on the GAPDH surface in the presence of resveratrol (decrease from -4.7mV to -9mV) [ 8 ]. The observed differences result from various pKa of both stilbene derivatives which determines the amount of protonated and nonprotonated forms at a specific pH.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Reduction of potential amounted from -5.1 ± 0.6 mV in the absence of the ligand to -11.2 ± 0.7 mV in its presence. Previous studies indicated slightly smaller changes of charge on the GAPDH surface in the presence of resveratrol (decrease from -4.7mV to -9mV) [ 8 ]. The observed differences result from various pKa of both stilbene derivatives which determines the amount of protonated and nonprotonated forms at a specific pH.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, piceatannol molecule locates inside the GAPDH, much further down the binding cleft as compared to resveratrol (the detailed location of RSV inside the GAPDH tetramer was presented by Rodacka et. al, 2015 [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have revealed that especially the 4'-OH group in the phenol ring of resveratrol dominates in the radical-scavenging efficiency and it is responsible for its biological activity (Stojanović et al 2001). The free-radical scavenging mechanism utilized by resveratrol involves the generation of 4'-phenoxy radicals followed by semiquinone and quinone structures (Rodacka et al 2015). It also improves endogenous Food Chemistry and Safety doi: 10.17221/401/2015-CJFS cellular antioxidant systems -superoxide dismutase (SOD), catalase, glutathione peroxidase (GPx), and the content of glutathione (GSH).…”
mentioning
confidence: 99%